INFORMED CONSENT AS A GUARANTOR AND PROTECTOR OF THE PATIENT'S UNBREAKABLE AUTONOMY - Vásquez Barrantes, Melannya (2024)
: Informed consent is a fundamental element in the doctor-patient relationship, since it guarantees respect for the autonomy and rights of the patient. In Costa Rica, this ethical and legal principle has been recognized and strengthened through regulations and jurisprudence that promote its application in all areas of medical care. This article examines in detail the concept of informed consent, its importance in Costa Rican medical practice, its component elements, and the challenges that still persist in its effective implementation. Informed consent is a fundamental element in the doctor-patient relationship, since it guarantees respect for the autonomy and rights of the patient. In Costa Rica, this ethical and legal principle has been recognized and strengthened through regulations and jurisprudence that promote its application in all areas of medical care. This article examines in detail the concept of informed consent, its importance in Costa Rican medical practice, the elements that compose it, and the challenges that still persist in its effective implementation, especially in light of the pandemic that has recently hit the world.